"Using Facebook Lets Me Know What He is Doing:" Relational Uncertainty, Breakups, and Renewals in On-again/Off-again Relationships. Issue 5 (20th October 2019) - Blight, Michael G.; Ruppel, Erin K.; Jagiello, Kristy
ABSTRACT: Uncertainty is a central but understudied element of on-again/off-again relationships, in which partners experience at least one renewal after a breakup. The current study investigates uncertainty reducing behaviors both generally and on Facebook. College-aged Facebook users (N = 220) responded to closed-ended measures of relational uncertainty and number of breakups and renewals, and open-ended questions regarding reasons for breakups/renewals and relational uncertainty reduction strategies. Relational uncertainty was higher among participants in an "off" stage and those who reported a higher number of breakups. The most reported behaviors on Facebook were passive (e.g., viewing a partner's profile) and outside of Facebook were active (e.g., asking a mutual friend). These findings offer insight into the role of relational uncertainty in on-again/off-again relationships.